Pemberdayaan Masyarakat Desa Kadudampit Kecamatan Saketi Pandeglang Banten - Amat Hidayat; Meliana Kharisma Putri; Ferdiandi Ferdiandi; Ahmad Turhani; Ida Safitri; Ikhsan Almuzi (Gapenas Publisher, 2022)
Kadudampit Village is a village that needs attention, especially in improving human resources both from the educational, economic and social aspects. This is due to the low level of human resources in the village. The method of community service through student work lecture activities, namely community education and training is carried out in cyclical stages through seven stages: the preparation stage, the assessment stage, the alternative planning stage for activities, the action plan formulation stage, the activity implementation stage, the evaluation stage, and the termination stage. The results of community service activities consist of increasing public awareness of the importance of digitalization in early childhood education as seen from the increased attention of parents to improve children's education in Kadudampit Village through the synergy of teachers, parents and the community. The realization of a society that is aware of the law on sexual harassment and the community understands and understands the sanctions for violations caused by sexual harassment and what forms of sexual harassment are. Increased marketing of oyster mushrooms by way of counseling on how to package and market production as well as to provide understanding in the management of agricultural products in Kadudampit Village so that they can be used properly and improve the welfare of the community in the economic field. Then increase public understanding and participation in vaccinating and immunizing children without coercion, anxiety and fear in the context of preventing the transmission of Covid-19. The realization of a clean and healthy community environment, as well as increasing the interest and motivation of adolescents, youth and children in religion